The Level of Knowledge of Premenopausal Mothers About Menopause Before and After Counseling in the Congregation of Keluarga Allah Bandung - Feby Putri Natasya; Sapti Heru Widiarti (HM Publisher, 2022)
Menopause is a phase in which a woman no longer has a menstrual cycle for 12 months at a time. Sequence with or without symptoms. The process of menopause can cause a woman to be confused about her situation because she is experiencing something similar for the first time so she needs to make adjustments. This study aims to find differences in the level of knowledge of premenopausal mothers before and after counseling about menopause in the Congregation of Keluarga Allah Bandung. The research method is quantitative with a quasi-experimental design with a sampling technique using a purposive sampling method with a total of 40 respondents. The instrument used is a test that has been tested for validity and reliability and is declared valid and reliable. The results showed that there were differences in the level of knowledge before and after being given counseling, with a p-value of 0.000 (p <0.05).